Targeting Hsp90-Cdc37: A Promising Therapeutic Strategy by Inhibiting Hsp90 Chaperone Function - Wang, Lei; Li, Li; Gu, Kai; Xu, Xiao-Li; Sun, Yuan; You, Qi-Dong (Current Drug Targets, 2017)
Background & Objective: The Hsp90 chaperone protein regulates the folding, maturation and stability of a wide variety of oncoproteins. In recent years, many Hsp90 inhibitors have entered into the clinical trials while all of them target ATPase showing similar binding capacity and kinds of side-effects so that none have reached to the market. During the regulation progress, numerous protein- protein interactions (PPI) such as Hsp90 and client proteins or cochaperones are involved. With the Hsp90-cochaperones PPI networks being more and more clear, many cancerous proteins have been reported to be tightly correlated to Hsp90-cochaperones PPI. Among them, Hsp90-Cdc37 PPI has been widely reported to associate with numerous protein kinases, making it a novel target for the treatment of cancers. Results and Conclusion: In this paper, we briefly review the strategies and modulators targeting Hsp90-Cdc37 complex including direct and indirect regulation mechanism. Through these discussions we expect to present inspirations for new insights into an alternative way to inhibit Hsp90 chaperone function.
Keywords: Hsp90/Cdc37